Environmentally friendly polymer nanocomposites - Ray, Suprakas Sinha 1973- (Woodhead Publishing Ltd, 2013)
Concerns about global warming and the depletion of oil reserves have led to significant research into more sustainable composite materials made from natural materials. Recently, research has focussed on the development of nanoscale reinforcements for this new group of composites, significantly improving and extending their range of desirable properties. Environmentally friendly polymer nanocomposites summarises this wealth of research and its practical implications. After an introduction to the subject, part one looks at matrix and reinforcement materials as well as their characterisation. Part two reviews key properties such as tensile and dynamic mechanical properties and thermal stability. It also considers issues such as barrier properties, biodegradability, rheology, electrical and thermal conductivity. The book concludes by reviewing potential applications. This book is ideal for polymer and material scientists, researchers and engineers. It will also help industrial researchers and R & D managers who want to bring advanced eco-friendly polymer composite-based products into the market. Summarises the practical implications of the development of nanoscale reinforcements for sustainable composite materials made from natural materialsExamines matrix and reinforcement materials and their characterisation and reviews key properties such as tensile and dynamic mechanical propertiesConsiders barrier properties, biodegradability, rheology, electrical and thermal conductivity and potential applications